Emergency admission, previous delirium tremens and increased liver stiffness as risk factors for severe alcohol withdrawal – A prospective study - Tobias Zellner; Jan-Christopher Metzger; Elias Bekka; Matteo Rabaioli; Konrad Stock; Minh-Truc Vo-Cong; Sabrina Schmoll; Eva-Carina Heier; Florian Eyer; Raphael Stich (PLoS ONE, 2025)
Objective To determine if increased liver stiffness (ILS) is a risk factor for patients with alcohol withdrawal to develop severe alcohol withdrawal symptoms (SAWS) like delirium tremens (DT) or withdrawal seizures (WS). Method Prospective inclusion of 394 patients undergoing withdrawal treatment between 2013-2021. Laboratory exams, history, physical examination, abdominal sonography with elastography and FibroScan® measurements were performed. Primary endpoint was SAWS defined as DT and/or WS. Patients with >  12.5 kPa stiffness in FibroScan® and >  1.75 m/s in Acoustic Radiation Force Impulse Imaging were considered ILS, patients with both measurements below the respective cut-off were ILS negative. Univariate analysis with receiver operating characteristic curve analysis and multivariate analysis were performed. Results 78 patients (19.8%) had ILS. Of these, 28 patients developed complications despite treatment. SAWS correlated significantly with patients with ILS. Further significant correlations were emergency hospital admission, Alcohol Withdrawal Scale ≥  5, lower potassium, elevated bilirubin, increased Gamma-GT, thrombocytopenia, previous WS, and previous DT. In multivariate binary regression analysis, odds ratio for SAWS was 5.4 for emergency admission, 3.5 for previous DT and 2.2 for ILS, even if the significance level for the last parameter was missed. Conclusions Patients with ILS have an increased risk of developing SAWS, as well as patients with emergency admission and previous DT among other markers. Treatment in an appropriately equipped facility is recommended for patients with this risk profile which can be measured easily by a general practitioner or in an emergency department.